ANALISIS STRATEGI PORTOFOLIO PRODUK KOPERASI SIMPAN PINJAM (Studi pada Koperasi Simpan Pinjam Karya Mandiri Jerowaru) - Sejarah Sejarah (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2016)
Research objectives are (1) to know in a position quadrant which each of product portfolio cooperatives ksp work mandiri, (2) to see how development strategy business unit corresponding to applied by cooperatives work mandiri.The kind of research used is research case study is descriptive.The majority of informants interviewed in spoke to as many as 5, namely Ahmad Zulyadaen, as manager cooperatives, Ahmat Rifai analyst credit, Muhamad Nuh as analyst credit, Sahrul Anam, as a survey and L. Jufri Ihsan as a board of trustees. Instrument data analysis with matrik market growth of boston consulting group (BCG).This method used to measure the magnitude of a business firm and controlling plans that is created in order assess estimates the profit produced. Based on the calculation on using the matrix bcg, so can be concluded that (1) Based on third bcg ksp matrix position of independent jerowaru in 2014-2015 be on the cash cow or dairy cows showing that the position of independent ksp jerowaru are on the market relative high the compete in industry slow growth. (2) are in cash cow quadrant indicates a reminder that the future of independent ksp jerowaru must try to innovation new products to make the market unsaturated, and existence company stay awake.Ksp the work of independent jerowaru should use a strategy of defense fort (fortress defense) consisting of two a cluster of the act of retracting, namely increase customer satisfaction and loyalty pelangan and action simplify to the buy back service by consumers / customers. Keywords: strategy, a matrix BCG